EPIDERMAL GROWTH FACTOR RECEPTOR AND PHOSPHODIESTERASE-4 AS THERAPEUTIC TARGETS IN ALLERGIC RHINITIS: A MOLECULAR DOCKING INVESTIGATION OF FLUTICASONE FUROATE AND AZELASTINE HYDROCHLORIDE - SUMITHA A; BRETHIS CS; KARTHIK VP; PURUSHOTHAMAN S; PUGAZHENDHI S (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Allergic rhinitis is an immunoglobulin E mediated reaction in the nasal mucosa to inhaled allergens, which affects the quality of life of people. Existing therapies provide inadequate symptom control, which drives investigation of targets in allergic rhinitis, such as epidermal growth factor receptor (EGFR) and phosphodiesterase-4 (PDE-4). Targeting EGFR reduces mucus hypersecretion, epithelial-driven inflammation, and alleviates allergic rhinitis symptoms. PDE-4 inhibitors suppress allergic inflammation. Hence, in this study, we employed docking to study the interactions of fluticasone furoate and azelastine hydrochloride against EGFR and PDE-4. Methods: Molecular docking was performed using AutoDock Tools 1.5.7 and Molegro molecular viewer. Ligands were optimized using the Merck molecular force field 94 force field. EGFR (Protein Data Bank [PDB] ID: 3POZ) and PDE-4 (PDB ID: 4NW7) structures were retrieved from the PDB. Grid box dimensions were set to 60×60×60 Å, spacing at 0.375 Å, and exhaustiveness was set at 8. Redocking of TAK-285 with EGFR was done to validate the docking protocol. Interactions were analyzed using Discovery Studio Visualizer. Results: Fluticasone furoate showed stronger binding affinities to EGFR (−9.24 kcal/mol) and PDE-4 (−9.27 kcal/mol) compared to azelastine hydrochloride (−7.15 and −9.23 kcal/mol, respectively). It formed hydrogen bonds and hydrophobic interactions with key residues in both proteins. In contrast, azelastine exhibited fewer interactions. Redocking of TAK-285 confirmed the docking protocol with root mean square deviation <2.0 Å. Conclusion: Fluticasone furoate demonstrates greater potential to inhibit EGFR and PDE-4, which are pivotal in allergic rhinitis treatment. This study results need further experimental and clinical validation for use in allergic rhinitis patients.